2012
DOI: 10.1186/1475-2840-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoluminal interventional therapy in diabetic peripheral arterial occlusive disease: a retrospective trial

Abstract: BackgroundThe purpose of this study was to assess the efficacy of interventional therapy for peripheral arterial occlusive disease and the difference between diabetic patients and non-diabetic patients.Methods139 consecutive patients between September 2006 and September 2010 who underwent percutaneous lower extremity revascularization for arterial lesions were divided into diabetes group (n = 62) and non-diabetes group (n = 77). Before intervention, rest ankle brachial indexes and three dimensional computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…ABI is defined as reliable marker for definition PAD, despite numerous factors that influence its value [39]. We measured progression of peripheral atherosclerosis using this index.…”
Section: Discussionmentioning
confidence: 99%
“…ABI is defined as reliable marker for definition PAD, despite numerous factors that influence its value [39]. We measured progression of peripheral atherosclerosis using this index.…”
Section: Discussionmentioning
confidence: 99%
“…Lejay et al [32] reported at 1 year the infra-popliteal arteries primary patency rates and limb salvage rates for PTA were 60% and 85%, respectively. In a contrast study between PTA and atherectomy of infra-popliteal arterial occlusive disease, Semaan et al [33] reported primary patency of the popliteal artery at 12 months were 75% and 73%, respectively, but the difference was not statistically significant. In our study, 6, 12 months primary patency rate for tibial arterial lesions with or without diabetes were 75%, 53.8% and 73.7%, 55.3%.…”
Section: Efficacy Of Different Studiesmentioning
confidence: 98%
“…Bảng 3: Thái độ của học sinh về hút thuốc lá (n=3873) Hút shishsa có hại cho sức khoẻ của bạn 155(4,0) 62 (1,6) 397 (10,3) 3242(83,7) 17(0,4) Hút thuốc lá điện tử có hại cho sức khoẻ của bạn 149 (3,9) 103(2,7) 399 (10,3) 3207(82,8) 15(0,4)…”
Section: Thái độ Của Học Sinh Từ 13-15 Tuổi Về Hút Thuốc Láunclassified
“…Nghiên cứu của Nguyễn Xuân Thanh (2015) bệnh nhân nữ là 56,8%, nam là 43,2%. 10 Sự khác biệt của các nhà nghiên cứu cũng không có ý nghĩa thống kê.…”
Section: Kết Quả Ghi Nhậnunclassified